Developing Learning Material of Descriptive Text Contained Lombok Local Culture for High School Students - Hilmiati Hilmiati; Anita Listiawati (Journal of Innovation in Educational and Cultural Research, 2022)
The availability of teaching materials for Indonesian language subjects in schools both at the junior high and high school levels in Lombok is quite a lot, but it is still very rare to integrate the topics of discussion with local culture. This condition became the basis of research on the development of integrated teaching materials on local Lombok wisdom. This study aims to develop descriptive text teaching materials containing the local culture of Lombok. There are four texts developed, namely (1) The life of women in Sade Village, (2) Men of Sade Village, (3) House Decorations, and (4) Materials for the Traditional House of Sade Village. This research is a development research by adopting the Reiser and Mollenda model known as ADDIE which consists of several steps, namely (1) analysis, (2) planning, (3) development, (4) implementation, and (5) evaluation. Research data in the form of numeric and test descriptions. The results showed that the Descriptive Text Learning Materials Containing Local Lombok Culture were declared valid and reliable so that they could be used in teaching and learning activities. The existence of this descriptive text material is expected to help teachers in the learning process. This research still needs to examine the effectiveness of learning outcomes so that further research needs to be done.